Pengembangan Media Pembelajaran Matematika Menggunakan Vidio Animasi di SD Kelas Awal - Rani Pitriani; Erwin Rahayu Saputra (Peneliti.net, 2021)
The rapid development of information and communication technology media is also a sign of the times. In the world of education, technology is seen as a challenge behind the emergence of the use of technology-based learning media. In the 21st century technology has become a necessity for the world of education. The use of technology as a learning medium is seen as effective in increasing the imagination of students. Especially in learning mathematics which is seen as terrible because it is difficult to understand. In the end, mathematics learning has little interest. Responding to this, the author presents an idea set forth in this article about changes regarding the development of mathematics learning media in elementary schools in the form of animated videos. The goal is to increase and attract students' interest and talents in learning mathematics so that later there will be a sense of pleasure in learning mathematics. As well as providing stimulation and understanding that mathematics is not difficult.